Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1074/jbc.m112.376095
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species-mediated Immunity against Leishmania mexicana and Serratia marcescens in the Phlebotomine Sand Fly Lutzomyia longipalpis

Abstract: Background: Reactive oxygen species are part of the sand fly innate immune system. Results: ROS production in the gut increases in response to a bacterial pathogen but not to Leishmania. Conclusion: Sand flies tolerate the presence of Leishmania by differential response of the ROS system. Significance: The successful use of sand flies as vehicles for Leishmania transmission relies partially on the parasite circumventing the ROS immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 45 publications
(1 reference statement)
1
74
0
Order By: Relevance
“…3E) have close relationship with ROS degradation (36,44). Transcription of these three genes in integument was higher toward the end of the larval-larval molting stage (Fig.…”
Section: Successful Ecdysis Is the Results Of Systematic Regulation Bymentioning
confidence: 99%
“…3E) have close relationship with ROS degradation (36,44). Transcription of these three genes in integument was higher toward the end of the larval-larval molting stage (Fig.…”
Section: Successful Ecdysis Is the Results Of Systematic Regulation Bymentioning
confidence: 99%
“…2A-C) indicating that promastigotes do not increase glucose uptake under stressful conditions. Analysis of metabolic flux revealed that H 2 O 2 , menadione, and diamide stimulated a metabolic reconfiguration from glycolysis toward PPP indicated by marked increase in 14 CO 2 evolution from [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]D-glucose whereas CO 2 evolution after utilization of [6][7][8][9][10][11][12][13][14] C]D-glucose did not significantly alter in Figure 6. Characterization of G6PDH and TAL overexpressing (OE) cell lines against wild-type (WT) cells transfected with empty vector.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, methylene blue, known to create intracellular oxidative stress by disrupting NADPH:NADP ratio, also had an similar effect on L. mexicana promastigotes (30). Cells cotreated with NAC in case of exposure to H 2 O 2 and menadione and GSH in case of diamide showed a decrease in 14 CO 2 evolution from [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]D-glucose indicative of ROS-mediated shifting of metabolic flux toward PPP from glycolysis. The glucose consumption assay also reinforced our observation by demonstrating that the glucose uptake pattern (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leishmania can manipulate the sand fly potentially threatening digestive proteases activity (Borovsky and Schlein 1983, Schlein et al 1983, Dillon and Lane 1993, Schlein and Jacobson 1998, Telleria et al 2010 and also can cause damage to the stomodeal valve of the fly (Schlein et al 1992, Rogers et al 2008, potentiating transmission. On the other hand, sand flies can mount an immune response to Leishmania infection (Boulanger et al 2004, Ramalho-Ortigão et al 2007, Jochim et al 2008, Pitaluga et al 2009, Diaz-Albiter et al 2012, Telleria et al 2012.…”
mentioning
confidence: 99%